Ampliación del tamizaje de errores innatos del metabolismo en Perú: reporte de caso con trastorno del metabolismo de cobalamina - Abarca-Barriga, Hugo Hernán (2020)
Neonatal screening for innate metabolism disorders was instituted more than 50 years ago. In Latin America, countries like Uruguay, Costa Rica, Chile, Brazil, and Colombia have implemented this public health measurement in a sustained fashion. Technology for detecting these conditions has been steadily progressing, achieving a good cost/effectiveness ratio, so access for such test is practically universal. Intracellular cobalamin metabolism disorders constitute a heterogeneous group that is subdivided in three biochemical phenotypes. We report the first patient in Peru with a late diagnosis of a homozygous c.394 C>T variant in the MMACHC gene, which belongs to the cbIC complementation group, which leads to methyl-malonic aciduria and homocystinuria, characterized by low height, retardation of psychomotor development, seizures, megaloblastic anemia, and variable thrombocytopenia and neutropenia. Also, homocysteine levels are high, there is methyl-malonic academia, and there is a paradoxical vitamin B12 increase in peripheral blood. This paper emphasizes the importance of making a timely diagnosis of potentially treatable conditions, avoiding or reducing the severity of the implied phenotype, with the implementation of new technologies in our country.